Mídia online: direito das mulheres à amamentação prolongada na perspectiva de gênero - Ignatios, Mariana Nunes (2020)
Although scientific evidence supports the clear benefits of breastfeeding for the mother, baby, family, society and our environment, there is limited improvement in this regard, and the key indicators remain stagnant. To amplify the practice of breastfeeding, efforts in several social fronts will be necessary. Early start, along with exclusive and continuous practice of breastfeeding are influenced by key factors such as social trends, media awareness and the availability of products in the market. Among these, media is an important factor to influence and stimulate breast feeding The present study has the objective of analyzing online media, more specifically Globo G1's coverage of prolonged breastfeeding, considering gender and human rights aspects. It is a documental study, exploratory,descriptive and qualitative in nature, utilizing themes from the G1 site. The data set was retrieved using Google, and includes news items from 2012 to 2018. The starting date was chosen based on a cover page article of Time Magazine, where prolonged breast feeding was featured, and which spread throughout the world. Content Analysis method was used to classify the news items. The results indicate that, although breast feeding practice involves directly the mother-woman, their own expectations, needs and livehood are not taken into consideration. The majority of pro-breastfeeding articles continue to focus on the importance of the practice due to benefits to the babies health. In that context, the female body continues to be regulated socially rather than focusing in the intersubjective process between mothers and their spouses, family and society. We conclude that media does not play a satisfactory role, often reproducing gender stereotypes that do not help women and families in their decision making process. We confirm that media has an important roleto play with relation to themes and modern pro-breastfeeding policies and their effects on womens' perspectives. We conclude that media has to bring together the theme of mother-woman, their needs and expectations, when breastfeeding is the focus when trying to improve indicators. It must also re-think its own role in reproducing norms and sexist conducts.